Phytochemical screening and antibacterial activities of crude extract of Nymphaea lotus (water lily) against fish pathogens - Adelakun, Kehinde Moruff; Mustapha, Moshood Keke; Muazu, Mohammed Muazu; Omotayo, Olabode Lawrence; Olaoye, Olanrewaju (Journal of Biomedical Sciences, 2016)
Background This study was designed to determine the role of aqueous extract of water lily (Nymphaea lotus) for potential antibacterial activity against some gram-negative fish pathogenic bacteria. Material and methods Aqueous extracts of the dried whole plant Nymphaea lotus was tested by the agar disc diffusion method against four bacteria strains, namely, Escherichia coli, Vibrio anguillarum, Pseudomonas fluorescens, Aeromonas hydrophila and Salmonella typhi. Inhibitory growth values were determined in colony forming unit per gram (cfu/g) for each pathogen while examination of phytochemical constituents of the crude extricate of the plant was also carried out qualitatively. Results Phytochemical screening of the crude aqueous extract revealed the high presence of saponins, alkaloids and carbohydrate, moderate presence of cardiac glycosides, tannins, phenolics, anthroquinones, terpenoid, quinones, catechins and trace of flavonoids. Conclusion The antibacterial analysis of crude aqueous extracts showed moderate varying degrees of resistance against the microbes especially Escherichia coli and Vibrio anguillarum where complete growth inhibition was observed. Hence, this plant aqueous extract can help in the treatment of fish bacterial infections. Journal of Biomedical Sciences. 2015;2(4):38-42.